2019
DOI: 10.1111/jgh.14877
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary and Pancreatic: Early palliative care referral in patients with end‐stage liver disease is associated with reduced resource utilization

Abstract: Background and Aims: Palliative care referral for end-stage liver disease (ESLD) is uncommon and usually occurs late. We aimed to review the rate of early palliative care referral (EPCR) in ESLD patients, its associations, and its impacts on resource utilization and survival. Methods: A retrospective review of all patients with ESLD admitted to a single Hepatology Unit between 2013 and 2016. Inclusion criteria for study entry were at least two admissions for decompensated liver disease within a 6-month period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
1
30
1
Order By: Relevance
“…It is important to note that prolonging survival time should not be considered a primary goal of palliative care consultation; rather, its goals are to improve quality of life, alleviate suffering symptoms, and support patients and families through their difficult times [ 47 ]. This study confirmed that palliative care consultation in HCC patients leads to a significant reduction in life-sustaining intervention, healthcare resource utilization, and cost, which was already proven in other conditions [ 23 , 48 , 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is important to note that prolonging survival time should not be considered a primary goal of palliative care consultation; rather, its goals are to improve quality of life, alleviate suffering symptoms, and support patients and families through their difficult times [ 47 ]. This study confirmed that palliative care consultation in HCC patients leads to a significant reduction in life-sustaining intervention, healthcare resource utilization, and cost, which was already proven in other conditions [ 23 , 48 , 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 83%
“…Some physicians believe that palliative sedation therapy is the same as slow euthanasia or terminal sedation, which hasten death [ 20 ]. There was an increase in evidence that negates these misbeliefs over the past years [ 21 , 22 , 23 , 24 ]; however, most studies were conducted in patients with end-stage liver disease or other cancers. This study aimed to provide causal evidence for the effect of palliative care consultation on the survival time after diagnosis and healthcare utilization in patients with HCC through emulation of a target trial from observational data.…”
Section: Introductionmentioning
confidence: 99%
“…From a resource perspective, palliative care involvement has also been shown to reduce readmission rates, economic costs, and hospital resource usage in ESLD 73 . In the aforementioned study on costs associated with HCC care, which showed terminal care was the most expensive phase, over half of terminal phase costs were attributed to acute inpatient care, while only 4.1% came from home care 5 .…”
Section: Lessons From Palliative Care For End‐stage Liver Diseasementioning
confidence: 99%
“…( 10 ) In an analysis of a nationwide inpatient sample, Rush et al ( 11 ) found that only 4.5% of all ESLD‐related admissions received a PC consultation, although this increased from 1% in 2006 to 7.1% in 2012. Barnes et al ( 12 ) found that only 19% of eligible patients (defined as having ≥ 2 admissions within 6 months for decompensated cirrhosis, excluding those who were listed for liver transplantation [LT]) received “early PC” (i.e., as defined by, PC received > 30 days before death), with hospitalization costs significantly reduced in those with early PC because of a lower number of endoscopies and blood transfusions. Similarly, studies have shown that less than 20% of patients removed from the LT waiting list received a PC consultation, and most of those occurred within 72 hours of death in an inpatient setting.…”
Section: Current State Of Pc For Esldmentioning
confidence: 99%